Analyzing Entrepreneurship Education Under COVID-19 - zhu, Fangyuan (International Journal of Management and Education in Human Development, 2022)
ABSTRACT “Entrepreneurship education, broadly defined as the development of pioneering individuals, is equally important to those who earn a salary, because employers or individuals are placing increasing emphasis on Employed initiative, risk-taking, entrepreneurial and independent work ability and technical, social and managerial skills”. Entrepreneurship education is an educational activity that enables educated people to innovate in social, economic, cultural and political fields, open up or expand new development space, and provide opportunities for others and society. Due to the enormous global impact of COVID-19 on society, new entrepreneurial education management practices are needed to cope with this change. Could COVID-19 be a transformational opportunity for entrepreneurship education research due to new thought processes triggered by the pandemic? Keywords: COVID-19, Education, Entrepreneurship education.